Implementasi Arsitektur Publish Subscribe Pada Constrained Application Protocol (COAP) di Lingkungan Internet of Things (IoT) - Muhammad Fauzi; Adhitya Bhawiyuga (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The rapid development of information technology makes the implementation of Internet-of-Things (IoT) increasingly common in everyday life. The IoT challenge is the ability to support devices with limitations and the Constrained Application Protocol (CoAP) is built to accommodate those problems. CoAP uses a client/server architecture that serves the request and provides the data respond requested by the user. This poses a problem when the client accesses the same resource simultaneously. This situation affects the workflow and makes it inefficient since it must do the same data request for all clients who needs that data. These activities may affect the performance of the server nodes which has limitations, and interfere the data transactions on the CoAP network. Therefore, the solution is by implementing a publish/subscribe architecture on CoAP in an IoT environment. The system uses broker that become bridges between publishers and subscribers, as well as data centers during data transactions. The test results show that the system has been able to run according to its functional needs, and the system has been able to run scalability test scenarios up to 250 users with a 0% error rate and has an average latency value of 74.5% smaller and overhead efficiency is 45.4% better than conventional CoAP. Based on these results, the system can be a solution to the problem of the IoT environment that has limitations.